2007
DOI: 10.1007/s11431-007-0001-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical studies of nickel deposition from aqueous solution in super-gravity field

Abstract: The effect of super-gravity on electrochemical deposition of nickel from aqueous solution was studied. The SEM pictures show that the microstructure of nickel film deposited under the super-gravity condition is finer and more uniform compared with that obtained in normal gravity condition, and the crystal grains diminish with the increase of super-gravity coefficient. The XRD patterns indicate that the arrangement of crystalline grains of nickel film deposited under the super-gravity field is more regular, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 5 publications
1
8
0
1
Order By: Relevance
“…Ni and Fe foils were electrodeposited under a supergravity field in our previous studies . It was found that the grains of all metal foils were refined by using a supergravity field.…”
Section: Functional Films Obtained Under a Supergravity Fieldsupporting
confidence: 71%
See 1 more Smart Citation
“…Ni and Fe foils were electrodeposited under a supergravity field in our previous studies . It was found that the grains of all metal foils were refined by using a supergravity field.…”
Section: Functional Films Obtained Under a Supergravity Fieldsupporting
confidence: 71%
“…Under a supergravity field, the bubbles moved with an arc, owing to inertia. The bubble separation went through point contact, and the contact time of the bubbles on the electrode surface was shortened under a supergravity field, so that the growth of bubbles was inhibited. The critical radii ( r G ) of bubbles and the driving force ( F G ) for bubble separation under a supergravity field are given as Equations (5) and : rG=-2σΔnormalGV×P0P0+ρ1Ggh FG=43πρ1-ρgGgrG3 …”
Section: Bubble Separation Under a Supergravity Fieldmentioning
confidence: 99%
“…Metallization of the silicon for microelectronic applications can be significantly enhanced by employing a super gravity field during the deposition process [25]. Furthermore, the super gravity field influences the morphology and the microstructure of deposits strongly [25][26][27][28]. For example, Cu metallization of silicon in the super gravity fields had smoother and denser surfaces [25].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…In order to improve the properties of iron foil, finer grains should be obtained during electrodeposition. The advantage of super gravity field on nickel electrodeposition from aqueous solutions has been observed [26]. It was found that both grain size and hydrogen content in nickel foil decreased with the increased gravity coefficient [26].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Therefore, it is significant to study the effects of gravity on the metal electrodeposition process, structures and properties of deposits. The applications of the super gravity field to the electrochemical deposition have received great interest [7][8][9][10][11][12]. The experiments in the super gravity field can be easily and cheaply achieved by centrifuges.…”
Section: Introductionmentioning
confidence: 99%